Upconversion nanoparticles for differential imaging of plant cells and detection of fluorescent dyes - 吴笑峰 胡盼 胡仕刚 陈增辉 严焕元 唐志军 席在芳 余意 戴港涛 刘云新 (Journal of rare earths, 2016)
Upconversion NaLuF_4 nanoparticles were synthesized by the solvothermal method which could emit multicolor visible light under the excitation of 980 nm near-infrared（NIR） photons. These upconversion nanoparticles（UCNPs） with an acidic ligand could rapidly capture the basic rhodamine-B（RB） in plant cells to generate a close UCNPs@RB system. RB could efficiently absorb the green fluorescence from NaLuF_4：18 mol.%Yb~（3＋）,2 mol.%Er~（3＋） UCNPs and then emitted red light in the UCNPs@RB system by a robust luminescence resonance energy transfer（LRET） from UCNPs to RB. The detection limit of RB with these upconversion fluorescent nanoprobes could reach 0.25 μg/cm~3 in plant cell even under an ultra low excitation power source of 0.2 W/mm2. This LRET phenomenon was also extended to Na Lu F4：18 mol.%Yb~（3＋）,0.5 mol.%Tm~（3＋）@Sodium fluorescein（SF） system. In addition, the differential imaging could be achieved by successively incubating plant cells with fluorescent dyes and UCNPs. The fluorescent dyes aggregated in cell wall while UCNPs with surface modification distributed both in cell wall and cytoplasm, so that UCNPs@Dyes formed in cell walls which could emit multicolor light by LRET which was different from the emission in cytoplasm with only UCNPs.